2023
DOI: 10.3390/plants12071498
|View full text |Cite
|
Sign up to set email alerts
|

Kin Recognition in an Herbicide-Resistant Barnyardgrass (Echinochloa crus-galli L.) Biotype

Abstract: Despite increasing evidence of kin recognition in natural and crop plants, there is a lack of knowledge of kin recognition in herbicide-resistant weeds that are escalating in cropping systems. Here, we identified a penoxsulam-resistant barnyardgrass biotype with the ability for kin recognition from two biotypes of penoxsulam-susceptible barnyardgrass and normal barnyardgrass at different levels of relatedness. When grown with closely related penoxsulam-susceptible barnyardgrass, penoxsulam-resistant barnyardgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Plants can distinguish their conspecific neighbors based on their genetic relatedness (i.e., kin recognition) and adjust their ‘behavior’ accordingly (i.e., kin discrimination) [ 150 ]. Such kin recognition and kin discrimination have been observed in individuals [ 151 ], populations, biotypes [ 122 , 152 ], and cultivar levels [ 87 ]. Kin recognition and kin discrimination allow behaviors toward kin groups.…”
Section: Allelobiosis and Plant Identity Recognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants can distinguish their conspecific neighbors based on their genetic relatedness (i.e., kin recognition) and adjust their ‘behavior’ accordingly (i.e., kin discrimination) [ 150 ]. Such kin recognition and kin discrimination have been observed in individuals [ 151 ], populations, biotypes [ 122 , 152 ], and cultivar levels [ 87 ]. Kin recognition and kin discrimination allow behaviors toward kin groups.…”
Section: Allelobiosis and Plant Identity Recognitionmentioning
confidence: 99%
“…Subsequent studies have shown that many plants are able to differentiate relatives from unrelated plants from the same population. Such kin recognition occurs in various types of plant species, ranging either from gymnosperms to angiosperms, or from wild species to crop plants [ 87 , 122 , 152 , 155 , 156 ]. The ability to detect relatedness would allow plants to discriminate closely from distantly related neighbors and optimize response strategies for the composition of their local neighborhood [ 6 , 150 , 157 , 158 ].…”
Section: Allelobiosis and Plant Identity Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the fitness cost of resistance and its mechanisms in herbicide-resistant weeds have been investigated and interpreted from molecular, physiological, and biochemical perspectives [17,22,[25][26][27][28], few studies, to our knowledge, involve phytochemical cues. In fact, phytochemicals, either endogenous hormones or exogenous signals and allelochemicals, play vital roles in plant growth, defense, and reproduction [29][30][31][32]. In particular, phytochemical signals can regulate the tradeoff between growth and defense and aboveground and belowground performance, and thus alter plant fitness [33].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Midzi et al [ 16 ] highlight the ecological relevance of such interactions under various environmental stresses and the growing understanding of the mechanisms involved and the significance of VOC-mediated inter-plant interactions under both biotic and abiotic stresses. As an interesting example of inter-plant interactions, Le Ding et al [ 17 ] show that intraspecific kin recognition may facilitate cooperation between genetically related biotypes to compete with interspecific rice, offering many potential implications and applications in paddy systems.…”
mentioning
confidence: 99%